Transoral endoscopic approach versus transcervical with or without mandibular swing approach to parapharyngeal space- a retrospective cohort study in a tertiary care center in Tamil Nadu - Krishnappa, Sheetal; N., Nikisha G. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of this study was to evaluate and compare patient outcomes and advantages of endoscopic transoral approach to parapharyngeal space with other approaches like transcervical with or without mandibular swing approach. Methods: In this retrospective cohort study, we have reviewed 13 cases of parapharyngeal space tumors resected with either trans oral endoscopic assisted approach or external approaches such as trans cervical and mandibular swing approach during the period of June 1, 2015 to May 31, 2020. Results: A total of 13 cases were included in the study. Among 13 cases, 9 were operated by transoral endoscopic approach, 2 by transcervical approach and 2 by transcervical with mandibular swing approach. Operative time (p=0.048), blood loss (p=0.028), hospital days (p=0.02) and postoperative patient satisfaction (p=0.008) were more in transoral route compared to transcervical route. Conclusions: Transoral endoscopic route is a safe route of surgery with less morbidity, less complications, less chance of neurovascular injury and cosmetically more acceptable for the patient when compared to open procedures for smaller size tumors without vascularization, present in the upper part of the parapharyngeal space and without attachment to any neurovascular structures.